2015
DOI: 10.1007/s00467-015-3095-5
|View full text |Cite
|
Sign up to set email alerts
|

Basal metabolic rate in children with chronic kidney disease and healthy control children

Abstract: It seems reasonable to use estimated average requirement as the basis of energy prescriptions for children with CKD (mean CKD stage 3 disease). However, those who were sicker had significantly lower metabolic rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…The KDOQI guidelines recommended an intake of 100% of estimated energy requirements (EER) of healthy children ( 5 ). In one study, the basal metabolic rate was similar in children with CKD compared to matched healthy children ( 25 ). In children with a GFR <75 ml/min/1,73 m 2 , an EER of 85–98% maintained acceptable growth ( 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…The KDOQI guidelines recommended an intake of 100% of estimated energy requirements (EER) of healthy children ( 5 ). In one study, the basal metabolic rate was similar in children with CKD compared to matched healthy children ( 25 ). In children with a GFR <75 ml/min/1,73 m 2 , an EER of 85–98% maintained acceptable growth ( 26 ).…”
Section: Discussionmentioning
confidence: 98%
“…There have been two strategies to investigate the optimal requirements for energy for children with CKD since publication of the KDOQI guidelines. First, four trials studied REE/ basal metabolic rate (BMR) by indirect calorimetry and showed no difference from healthy children after adjustment for lean body mass (14)(15)(16)(17). One trial measured BMR by indirect open circuit calorimetry in 20 children with CKD and 20 healthy age-and gender-matched controls (17).…”
Section: Evidence and Rationalementioning
confidence: 99%
“…However, factors such as inflammation or comorbidities may increase caloric needs in later stages of CKD even if basal rates decreases. It is prudent to assume estimated energy requirement (EER) calculations, used with healthy children, are a good starting place to estimate needs and adjust as needed based on the child's growth (29). However, barriers such as appetite, uremia, and inflammation may impair the ability for children to receive the calories they need.…”
Section: Factors Affecting Enteral Nutrition Choicesmentioning
confidence: 99%